Eye Movements in Real-World Scene Photographs: General Characteristics and Effects of Viewing Task - Cronin, Deborah A.; Hall, Elizabeth H.; Goold, Jessica E.; Hayes, Taylor R.; Henderson, John M. (Frontiers in Psychology, 2020)
The present study examines eye movement behavior in real-world scenes with a large (N=100) sample. We report baseline measures of eye movement behavior in our sample, including mean fixation duration, saccade amplitude, and initial saccade latency. We also characterize how eye movement behaviors change over the course of a 12 second trial. These baseline measures will be of use to future work studying eye movement behavior in scenes in a variety of literatures. We also examine effects of viewing task on when and where the eyes move in real-world scenes: participants engaged in a memorization and an aesthetic judgement task while viewing 100 scenes. While we find no difference at the mean-level between the two tasks, temporal-and distribution-level analyses reveal significant task-driven differences in eye movement behavior.